Facile construction of high-performance 3D Co2C-doped CoAl2O4 fiber composites for capturing and decomposing tetracycline from aqueous solution - Cao, Mengbo; Liu, Xun; Yang, Hongbing (Journal of hazardous materials, 2022)
Herein, novel 3D hollow-carved Co2C-doped CoAl2O4 fiber composites (3D-CA-FC) were successfully synthesized via a simple-green pyrolysis method and exhibited remarkably outstanding elimination performance for tetracycline (TC) by adsorption and degradation. The results indicated that the TC adsorption process of the samples could be accurately described by the pseudo-second-order and Langmuir isothermal model, and the maximum TC uptake reached up to 1889.63 mg/g under neutral conditions. Meanwhile, 3D-CA-FC showed good affinity for TC and its adsorption capacity was greatly promoted due to the presence of humic acid, CO32- ion and weakly alkaline environment. About complete degradation of TC could be completed within 60 min under suitable conditions. A significant improvement of catalyst rate was observed after the addition of CO32- ion, because of the selective degradation of CO3•- to TC. BET, XPS and FT-IR analysis indicated that the mechanisms of TC uptake can be ascribed to pore-filling, H-bonds and complexation. Radical trapping experiments showed that 1O2 should serve as predominant contributions, and SO4•- and •OH also played a role in the degradation process. This study provides some inspiration for the construction of 3D-CA-FC as a novel and promising bifunctional material for the elimination of contaminants in water treatment. [Display omitted] •Co2C-doped CoAl2O4 fiber composites were successfully prepared by pyrolysis method.•Fiber composites show both excellent adsorption and degradation capacity towards TC.•CO32- promoted the TC adsorption on the sample and the degradation rate by oxidation.•Adsorption mechanisms are pore-filling, H-bonds and complexation.•1O2 serve as predominant contributions in the degradation process.